The application of rhubarb concoctions in traditional Chinese medicine and its compounds, processing methods, pharmacology, toxicology and clinical research - Wen, Yi; Yan, Pei-Jia; Fan, Pei-Xuan; Lu, Shan-Shan; Li, Mao-Ya; Fu, Xian-Yun; Wei, Shao-Bin (Frontiers in Pharmacology, 2024)
OBJECTIVE: This study reviews the development of rhubarb processing and the current status of pharmacological research. We summarized the effects of different processing methods on the active compounds, pharmacological effects, and toxicity of rhubarb, as well as the clinical application of different concoctions, providing reference for further pharmacological research and clinical application of rhubarb.METHODS: A comprehensive literature review was conducted using databases such as Pubmed, Embase, National Science and Technology Library, Web of science, CNKI, China Science and Technology Journal Database, SinoMed, and the Pharmacopoeia of the People's Republic of China. Search terms included "rhubarb", "raw rhubarb", "wine rhubarb", "cooked rhubarb", "rhubarb charcoal", "herbal processing", "compounds", "pharmacological effects", "inflammation", "gastrointestinal bleeding" and "tumor".RESULTS: Historical records of rhubarb processing date back to the Han Dynasty, with continual innovations. Currently, the types of rhubarb used in traditional Chinese medicine have stabilized to 3 species: Rheum palmatum L., Rheum tanguticum Maxim.ex Balf. and Rheum officinale Baill.. Common concoctions include wine rhubarb, cooked rhubarb and rhubarb charcoal. The active compounds of rhubarb are known to defecation, exhibit antibacterial and anti-inflammatory properties, regulate coagulation, protect the digestive system, and possess anti-tumor activities. Guided by Chinese medicine theory, the use of different rhubarb concoctions can enhance specific effects such as purgation to eliminate accumulation, clearing heat and toxins, cooling blood to stop hemorrhages, activating blood circulation to remove blood stasis, and inducing dampness to descend jaundice, thereby effectively treating various diseases. The therapeutic impact of these concoctions on diseases reflects not only in the changes to the active compounds of rhubarb but also in the formulations of traditional Chinese medicine. Processing has also shown advantages in reducing toxicity. CONCLUSION: Different processing methods alter the active compounds of rhubarb, thereby enhancing its various pharmacological effects and meeting the therapeutic needs of diverse diseases. Selecting an appropriate processing method based on the patient's specific conditions can maximize its pharmacological properties and improve clinical outcomes.